Rhamnolipids Production by a Pseudomonas eruginosa LBI Mutant: Solutions and Homologs Characterization - Lovaglio, Roberta B. [UNESP]; Silva, Vincius L. da [UNESP]; Capelini, Tulio de Lucca [UNESP]; Eberlin, Marcos N.; Hausmann, Rudolf; Henkel, Marius; Contiero, Jonas [UNESP] (Carl Hanser Verlag, 2014)
This paper evaluates the effect of additives (NaCl and ethanol) on the solution properties of rhamnolipids. The properties are the surface activity, aggregate formations and emulsifying activity as well as the synergistic effects of additives and pH variations on the physical properties of rhamnolipids. Additionally, analysis of fatty acids and rhamnolipid homologues produced using different carbon sources was performed by mass spectrometry. The results indicate that this biosurfactant maintain its properties in the presence of additives. NaCl decreases the size and number of aggregates formed in solutions without pH control, while ethanol to rhamnolipid solutions reduces critical micelle concentration and favors aggregation of monomers. The profiles of fatty acids produced by P. aeruginosa LBI 2A1 varied according to the carbon source used, however for rhamnolipids there was no difference.
Keywords: Rhamnolipids; Pseudomonas aeruginosa LBI mutant; biosurfactant; physical properties; critical micelle concentration (CMC)